F-071IMPACT OF LYMPH NODE INVOLVEMENT AND ROLE OF LYMPHADENECTOMY IN THE SURGERY OF LUNG METASTASES OF COLORECTAL CANCER: RESULTS FROM THE SPANISH PROSPECTIVE COLORECTAL METASTASECTOMY REGISTRY. (June 2014) - Call, Sergi; Rami-Porta, R.; Embún, R.; Rivas De Andres, J.J.; Molins, L.; Belda-Sanchis, J.; ,
Abstract : Objectives: 1) To describe lymph node (LN) assessment and incidence of LN involvement in the Spanish registry. 2) To identify risk factors associated with thoracic LN spread. 3) To determine the impact of LN involvement on survival. Methods: Five hundred and twenty-two patients from 32 hospitals were prospectively registered from 2008 to 2010. Follow-up data were completed in March 2013. Lymphadenectomies were defined according to the definitions of the Bronchogenic Carcinoma Cooperative Group of SEPAR. For pathologic (p) N0, at least a systematic sampling was required, or the N status was coded as pNx. The relationship between clinical and oncological variables from colorectal episode to thoracic LN involvement was analysed by bivariate analysis. Overall survival (OS) and disease-free survival (DFS) were calculated by the Kaplan-Meier method with the log-rank test for comparisons. Cox regression analysis was used to estimate the hazard ratio (HR). Results: Lymphadenectomy was performed in 250 (48%) patients: 50 (20%) systematic nodal dissection, 87 (34.8%) systematic sampling and 113 (45.2%) minor lymphadenectomies. Median number of resected LNs was 4 (1-41). LN involvement was found in 25 (10%) patients. LN involvement was associated with the following variables from the primary tumour: The pT ( P < 0.05) and the site of the colorectal cancer (sigma; P < 0.05). The median OS and DFS of all series were 55 and 28.3 months, respectively. Regarding DFS, there are no significant differences among groups depending on the pN status. Conclusions: Lymphadenectomy in the Spanish metastasectomy registry was not uniformly performed. As a consequence, the incidence of LN involvement (10%) was slightly lower compared with other series. LN involvement remains an important prognostic factor associated with an increased risk of death and, therefore, an adequate intraoperative lymph node assessment should be performed in all metastasectomies. Disclosure: S. Call, R. Rami-Porta, R. Embún, J.J. Rivas de Andres, L. Molins, J. Belda-Sanchis, SEPAR GECMP-CCR. The GECMP-CCR-SEPAR database and the statistic analysis of this study have been funded by Ethicon-Endosurgery